ANTI-DIABETIC ACTIVITY OF ETHANOLIC EXTRACT OF ELAEOCARPUS SERRATUS L. IN STREPTOZOTOCIN-INDUCED DIABETIC RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
To investigate the anti-diabetic activity of Elaeocarpus serratus fruit in streptozotocin-induced (STZ) diabetic rats. The dose-dependent effects of 30days oral treatment with ethanol extracts of fruit (200 and 400 mg/kg) of E. serratus on body weight, blood glucose level, total protein, albumin, liver marker enzymes and carbohydrate metabolizing enzymes were evaluated in STZ-induced diabetic rats. Oral administration ethanolic extract of fruit of E. serratus showed significant restoration of the body weight and decrease in the blood glucose level, liver marker enzymes (ALT, AST ALP) and carbohydrate metabolizing enzymes were observed in diabetic rats. These results suggest that fruit extract of E. serratus has valuable anti-diabetic activity in STZ-induced diabetic rats which is comparable to the standard drug glibenclamide and hence might be of use in the management of diabetes.